HUBUNGAN ANTARA PERILAKU MENOLONG DENGAN KONSEP DIRI PADA REMAJA AKHIR YANG MENJADI ANGGOTA TIM BANTUAN MEDIS JANAR DUTA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Putra, I Dewa Gede Udayana; Rustika, I Made (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2015)
Self-concept is an important factor in Adolescents. These mental aspects determine human behavior in every cycle of life. Self-concept weren’t born from lineage mental aspect but these are build and grow from human interactions with their environment naturally. Helping others is a human nature tendencies, individual has basic need to provide and seeking help. After provide a help, somebody would feel proud of what they have been done so that will improve their self valuation. Helping behavior shows by adolescents whom join Tim Bantuan Medis Janar Duta Faculty of Medicine, Udayana University. This research aim to find out the relation of helping behavior with self-concept in late adolescents. Subject in this research is late adolescents whom join Tim Bantuan Medis (TBM) Janar Duta Faculty of Medicine, Udayana University. Sample in this research is 84 persons. Instrument in this research used helping behavior scale and self-concept scale. Analysis method that used is product moment analysis technique from Pearson. Results shows correlation in this research is 0.690 (p=0.000). It is conclude that there is a significant positive correlation between helping behavior and self-concept whom join Tim Bantuan Medis (TBM) Janar Duta Faculty of Medicine, Udayana University. Keywords: helping behavior, self concept, late adolescent